Shade management and pruning in two coffee varieties vs. plant growth and leaf rust in the Peruvian Amazon (Bioagro, 2022)
Coffee leaf rust (CLR) is a fungal infection which is devastating susceptible coffee plantations throughout the South American region in the last years. The objective of this study was to analyze the effects of shade trees management and pruning in two coffee varieties against coffee leaf rust in the Peruvian Amazon. The experimental design was a randomized complete block with factorial scheme 2A×2B×4C with 16 treatments and four repetitions, making a total of 64 experimental units, in which each experimental unit had 16 coffee plants. The studied factors were agroforestry system (A), coffee varieties (B), and pruning methods (C). The data were statistically examined by analysis of variance and mean comparisons using Tukey test. It was found that plant growth was favored by the use Inga shade and recepa pruning in Typica variety. Also, the use of polyculture-shaded coffee with about 40 % of shadow, and recepa, a pruning method which consists of cutting the stem of the coffee plants at 40 cm from the ground, reduce the incidence and severity of CLR in coffee plants. The incidence and severity of CLR was lower in the Typica variety as comparted to Pache variety. This study confirms that a shadow management and pruning coffee plants stimulate the growth of new branches and reduce incidence and severity of CLR in coffee plantations.
Keywords: Agroforestry system; CLR incidence and severity; Coffea arabica; recepa pruning